Rabbi with a Cause A Conversation with David J. Goldberg. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and David J. Goldberg (1939-2019), former Senior Rabbi Emeritus of London's Liberal Jewish Synagogue and author and columnist. This wide-ranging conversation is based on Goldberg's book, This Is Not The Way: Jews, Judaism and Israel, which boldly explores a number of themes that interweave religion, politics, culture and identity in a way that is relevant to all of us, regardless of our cultural background or religious orientation. For many of us, caught as we are between love of tradition and the allure of contemporar.